Effectiveness of turmeric (Curcuma Longa Linn) Gel Extract (GE) on wound healing: Pre-clinical test - Adeliana; Andi Nilawati Usman; Mardiana Ahmad; Sharvianty Arifuddin; Risfah Yulianty; Prihantono (Elsevier, 2021)
Objective: This research was basic research to identify the effect of turmeric extract tested by the in vivo method. The purpose of this study was to identify differences in the length of the wound at each concentration of gel preparations on days 3, 7, and 14, as well as differences in wound healing time at each concentration of gel preparations and, identify the most effective gel preparations for wound healing. Method: This study is an experimental laboratory study with experimental animals using post-test only with control groups, the type of research used is a pre-clinical test (pre-clinical trial) on female rabbits. The sample size in this study was 12 rabbits grouped randomly. The length of each group's wounds was measured and observed on days 3, 7, and 14. Gel application was carried out twice a day in the morning and evening for 14 days. In this study, the experimental data were tested using Kruskal Wallis. Results: There were differences in wound length in each group treated with turmeric extract gel and base gel. Based on the mean wound length of each group, they experienced a reduction in wound length on days 3, 7, and 14. There were also differences in wound healing time in each group. In each group, wherein this case, the treatment group that was given 5% turmeric extract gel experienced a faster healing time <14 days than the other groups. Conclusion: In general, turmeric extract gel at each concentration is effective against wound healing. Turmeric extract gel concentration is the most effective gel with a concentration of 5%, then followed by concentrations of 10% and 15%.